Anti-aging polyglycolic acid resin composition as well as preparation method and application thereof
By adding vinyl ester polyglycolic acid graft copolymer to polyglycolic acid and polybutylene terephthalate resins, the problem of easy degradation of PGA at high temperatures is solved, and the aging stability and mechanical properties of the composition are significantly improved.
Patent Information
- Application Number
- CN202311333264.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-18
AI Technical Summary
Pure polyglycolic acid (PGA) is prone to degradation during high temperature processing and has poor toughness. The added antioxidants and anti-hydrolytic agents may cause compatibility problems and consumption, resulting in poor mechanical properties stability.
By continuous twin screw extrusion, a polyglycolic acid graft copolymer with vinyl ester side chains is added to a blend of polyglycolic acid and polybutylene terephthalate-based resin to improve its aging performance.
The aging stability of the polyglycolic acid resin composition is significantly improved, and its stability and service life are enhanced at high temperatures.
Smart Images

Figure CN119842188A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to an aging-resistant polyglycolic acid resin composition and a preparation method and application thereof. Background Art
[0002] Polyglycolic acid (PGA) is a semi-crystalline aliphatic polyester polymer material with the least number of monomer carbons and is completely degradable. It has a high degree of crystallinity, generally 33-52%, and has the characteristic advantages of high strength and high modulus. At the same time, due to its excellent biocompatibility and rapid degradability, it has important applications in medical fields such as surgical sutures and tissue engineering scaffolds. However, pure PGA has weaknesses such as poor toughness, easy degradation during high-temperature processing, easy hydrolysis, and short shelf life, which makes it impossible to be directly used in daily disposable products.
[0003] In order to solve the problem of poor toughness of PGA, it is currently mainly melt-blended with other flexible degradable polyesters such as polyadipate / butylene terephthalate. In order to solve the problem that degradable polyesters are still easily degraded during high-temperature processing, Chinese patent CN109575536A discloses a polyglycolic acid composition, which melt-blends polyglycolic acid (PGA) with polybutylene terephthalate resin (PBAT), and increases its processing stability and service life by adding additives such as anti-hydrolysis agents and antioxidants. However, externally added antioxidants and anti-hydrolysis agents may cause compatibility problems between PGA and PBAT and are easily consumed during the aging process, and the mechanical properties are not stable and maintainable. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an aging-resistant polyglycolic acid resin composition and a preparation method and application thereof. The present invention adopts a continuous twin-screw extrusion method to add a polyglycolic acid graft copolymer having a vinyl ester side chain to a polyglycolic acid and polybutylene terephthalate resin blend, thereby improving the aging performance of the polyglycolic acid and polybutylene terephthalate resin blend.
[0005] One of the purposes of the present invention is to provide an aging-resistant polyglycolic acid resin composition, comprising: a mixture of polyglycolic acid, a polyglycolic acid graft copolymer, a polybutylene terephthalate resin and / or a reaction product thereof, wherein the polyglycolic acid graft copolymer is a copolymer of a vinyl ester compound or its derivative and polyglycolic acid.
[0006] According to the present invention, in the aging-resistant polyglycolic acid resin composition: based on the total mass of the polyglycolic acid, the polyglycolic acid graft copolymer and the polybutylene terephthalate resin as 100%, the polyglycolic acid accounts for 8.5-75%, the polyglycolic acid graft copolymer accounts for 0.5-20%, and the polybutylene terephthalate resin accounts for 5-91%; preferably, the polyglycolic acid accounts for 20-55%, the polyglycolic acid graft copolymer accounts for 1-15%, and the polybutylene terephthalate resin accounts for 30-79%.
[0007] According to the present invention, in the aging-resistant polyglycolic acid resin composition:
[0008] The weight average molecular weight of the polyglycolic acid is 100,000 to 1,000,000 g / mol, and the molecular weight distribution index (PDI) is 1.5 to 5; preferably, the weight average molecular weight of the polyglycolic acid is 100,000 to 500,000 g / mol, and the molecular weight distribution index (PDI) is 2 to 3;
[0009] The intrinsic viscosity of the polyglycolic acid is 0.9 to 7 dl / g, for example, the intrinsic viscosity can be any value among 0.9 dl / g, 1 dl / g, 2 dl / g, 2.5 dl / g, 3 dl / g, 3.5 dl / g, 4 dl / g, 4.5 dl / g, 5 dl / g, 5.5 dl / g, 6 dl / g, 6.5 dl / g, 7 dl / g or a value between any two of the above values. Preferably, the intrinsic viscosity of the polyglycolic acid is 1 to 5 dl / g;
[0010] The melt flow rate of the polyglycolic acid measured at 230° C. and 2.16 kg is 1 to 80 g / 10 min. For example, the melt flow rate of the polyglycolic acid is any value among 1 g / 10 min, 5 g / 10 min, 10 g / 10 min, 15 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, 40 g / 10 min, 45 g / 10 min, 50 g / 10 min, 60 g / 10 min, 70 g / 10 min, and 80 g / 10 min, or a value between any two of the above values. Preferably, the melt flow rate of the polyglycolic acid measured at 230° C. and 2.16 kg is 1 to 50 g / 10 min.
[0011] The polybutylene terephthalate resin is selected from the copolyester of aliphatic dibasic acid / terephthalic acid / polyol, preferably at least one of polybutylene adipate terephthalate and polybutylene succinate terephthalate;
[0012] The vinyl ester compound or its derivative is selected from fatty acid vinyl ester compounds or their derivatives, preferably at least one selected from vinyl acetate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl octadecanoate, divinyl adipate, and vinyl decanoate;
[0013] The weight average molecular weight of the polyglycolic acid graft copolymer is 90,000 to 300,000 g / mol, preferably 110,000 to 200,000 g / mol.
[0014] According to the present invention, the polyglycolic acid resin composition further comprises a functional aid, preferably, the functional aid is selected from at least one of antioxidant I and chain extender. The antioxidant I and chain extender can adopt the component compounds and dosages commonly used in the art, for example, the antioxidant I is selected from at least one of hindered phenols, hindered amines, phosphites, phosphates, and thiols; the chain extender is selected from at least one of multifunctional compounds or grafts containing multiple epoxy groups or isocyanate groups, preferably at least one of diphenylmethane diisocyanate, dioxazoline, glycidyl methacrylate, styrene-methyl methacrylate-maleic anhydride copolymer; based on the total mass of the polyglycolic acid, polyglycolic acid graft copolymer and polybutylene terephthalate resin as 100%, the antioxidant I is 0.1-5%, preferably 0.1-2%; the chain extender is 0.01-10%, preferably 0.01-5%. The polyglycolic acid resin composition may also be added with other processing aids commonly used in the art, such as an opening agent, which may be selected from fatty acid amide compounds, and is preferably selected from at least one of oleamide, erucamide, and stearamide.
[0015] The second object of the present invention is to provide a method for preparing the above-mentioned aging-resistant polyglycolic acid resin composition, comprising: fully mixing the components including the polyglycolic acid, polybutylene terephthalate resin, and polyglycolic acid graft copolymer, melt-blending and extruding, and cooling to obtain the aging-resistant polyglycolic acid resin composition.
[0016] According to the present invention, in the method for preparing the aging-resistant polyglycolic acid resin composition:
[0017] Before mixing, the polyglycolic acid, polybutylene terephthalate resin, and polyglycolic acid graft copolymer are dried. The drying may be carried out using drying equipment and drying conditions commonly used in the art, such as vacuum drying, hot air drying, etc. Specifically, the drying temperature is 10 to 80° C., preferably 10 to 40° C.; the water content of the polyglycolic acid after the drying is less than 100 ppm, preferably less than 80 ppm;
[0018] The melt blending extrusion operation can be achieved by using a twin-screw extruder. Specifically, the melt blending extrusion conditions are: the melt blending extrusion temperature is 180-260°C, and the extruder speed is 10-500rpm; preferably, the melt blending extrusion temperature is 190-250°C, and the extruder speed is 100-250rpm;
[0019] After melt blending and extrusion, the obtained material can be cooled, granulated and packaged by conventional operations, wherein cooling can be carried out by air cooling or water cooling.
[0020] According to the present invention, in the preparation method of the aging-resistant polyglycolic acid resin composition, a functional auxiliary agent is further added during the mixing process, and the functional auxiliary agent is selected from at least one of antioxidant I and chain extender. Wherein, the antioxidant I is selected from at least one of hindered phenols, hindered amines, phosphites, phosphates, and thiols; the chain extender is selected from at least one of multifunctional compounds or grafts containing multiple epoxy groups or isocyanate groups, preferably at least one of diphenylmethane diisocyanate, dioxazoline, glycidyl methacrylate, and styrene-methyl methacrylate-maleic anhydride copolymer; based on the total mass of the polyglycolic acid, polyglycolic acid graft copolymer, and polybutylene terephthalate resin as 100%, the antioxidant I is 0.1-1%, preferably 0.1-0.6%; the chain extender is 0.01-10%, preferably 0.01-5%.
[0021] According to the present invention, the polyglycolic acid graft copolymer is obtained by mixing a vinyl ester compound or its derivative with polyglycolic acid and subjecting it to a grafting reaction under the action of an initiator; preferably, a screw extruder is used for the grafting reaction.
[0022] Specifically, in the grafting reaction of the polyglycolic acid graft copolymer:
[0023] The initiator is selected from organic peroxide initiators, preferably at least one selected from tert-butylbenzene peroxide, dibenzoyl peroxide, and dicumyl peroxide;
[0024] The mass ratio of the vinyl ester compound or its derivative to the polyglycolic acid is 1:(10-200), preferably 1:(15-80);
[0025] Based on the total mass of the vinyl ester compound or its derivative and the polyglycolic acid as 100%, the initiator is 0.01-1%, preferably 0.07-0.2%;
[0026] The temperature of the grafting reaction is 140 to 260°C, preferably 150 to 240°C;
[0027] Antioxidant II is optionally added during the mixing process. Preferably, the antioxidant II is selected from at least one of hindered phenols, hindered amines, phosphites, phosphates, and thiols; based on the total mass of the vinyl ester compound or its derivative and polyglycolic acid as 100%, the antioxidant II is 0.1-5%.
[0028] According to the present invention, after the aging-resistant polyglycolic acid resin composition is subjected to 100 hours of xenon lamp accelerated aging, the elongation at break retention rate of the polyglycolic acid resin composition is greater than 25%, and the long-term change of the composition is ≤0.4nm.
[0029] The third object of the present invention is to provide an aging-resistant polyglycolic acid resin composition as mentioned above or an aging-resistant polyglycolic acid resin composition obtained by the above preparation method, which can be used in medicine, daily necessities, and oil production, and can be specifically applied to film bags, sheets, injection molded parts, straws, lunch boxes and other products.
[0030] The present invention provides an aging-resistant polyglycolic acid resin composition, a preparation method and an application thereof. After melt blending, extrusion, cooling and granulation, the obtained polyglycolic acid resin composition has excellent aging stability. The advantage of the present invention is that by adding a vinyl ester polyglycolic acid graft copolymer to a polyglycolic acid and polybutylene terephthalate resin biodegradable polyester, the dimensional stability of the composition before and after aging can be greatly improved, thereby improving the aging performance of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The polyglycolic acid resin composition films prepared in Comparative Examples 1 and 2 and Examples 2 and 3 undergo long-term changes during the aging process.
[0032] Figure 2 . The relationship between the elongation at break retention rate and aging time of the polyglycolic acid resin composition films prepared in Comparative Examples 1 and 2 and Examples 2 and 3, the abscissa is the aging time (h), and the ordinate is the elongation at break (%). DETAILED DESCRIPTION
[0033] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0034] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0035] Source of raw materials
[0036] The raw materials used in the examples and comparative examples are all commercially available.
[0037] Polyglycolic acid (PGA), produced by Corbion Purac of the Netherlands, has an intrinsic viscosity of 1.0-1.4 dl / g, a melting point of 221.4°C, and a melt flow rate of 46 g / 10 min at 230°C and 2.16 kg;
[0038] Polybutylene adipate terephthalate (PBAT), produced by BASF, Germany, brand C1200 FBlend, melt flow rate at 190°C, 2.16kg is 5.5g / 10min;
[0039] Chain extender, produced by BASF, Germany, brand ADR-4370.
[0040] Antioxidant, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, triphenyl phosphite, Nanjing Jingtianwei Chemical Company.
[0041] The present invention performs performance measurement according to the following method:
[0042] Melt flow rate (MFR) test: According to ISO 1133 standard, Lloyd Davenport MFI-10 / 230 melt flow rate tester was used for measurement, barrel temperature was 230°C, weight load was 2.16kg, die diameter was 2.095mm, length was 8mm, preheating time was 4min, automatic sample cutting was performed at set time intervals, 5 samples were taken for average, and the measurement results were expressed in grams per 10 minutes (g / 10min).
[0043] Thermogravimetric analysis (TGA) test: The test was conducted on the Discovery series thermogravimetric analyzer of THERMALANALYSIS, and the processing software was TAInstruments Trios 3.1.4. Before the test, the machine was preheated until the temperature of the balance cavity was stable at 40°C. During the test, 5-10 mg of sample was weighed and placed in a ceramic crucible, and the test was carried out in an air atmosphere with a flow rate of 20 mL / min. The temperature rise range was 30-600°C, and the heating rate was 10°C / min. The weight loss curve of the sample was recorded.
[0044] Film tensile test: According to ISO 527-3 standard, the 3344 universal testing machine of INSTRON was used for measurement, and the processing software was Bluehill 2.31 version. The sample was cut into Type 5 in ISO 527-3 standard and placed in the Bluepard BPS-100CB constant temperature and humidity chamber (temperature 23°C, relative humidity 50%) of Shanghai Yiheng Scientific Instrument Co., Ltd. for 24 hours. During the test, the initial clamp spacing was 50mm, the test tensile rate was 500mm / min, each sample was tested 5 times, and the average value was taken.
[0045] Accelerated aging test: In the UV accelerated aging test, the comparative and example films were placed in a xenon test chamber (Q-SUN Xe-3). The test sample was placed in a cavity fixed to an aluminum bracket. The irradiance of the device at a wavelength of 340nm was 0.51W / m 2 The temperature was set at 38°C and the humidity was maintained at 50%.
[0046] Small angle scattering (SAXS) test: light source energy up to 20keV, energy resolution 6*10 -4 @10keV, photon flux is 10 11 S -1 @10keV, the minimum measurable angle is 0.023°, the distance from the sample to the detector is 2.058m, the wavelength of the incident X-ray is 0.124nm, and the exposure time is 10s.
[0047] [Comparative Example 1]
[0048] Preparation of polyglycolic acid resin composition:
[0049] The polyglycolic acid particles and polybutylene adipate terephthalate particles were dried by hot air at a temperature of 35±2°C for 2 hours. 25 parts of polyglycolic acid (PGA, Corbion Purac) and 75 parts of polybutylene adipate terephthalate (PBAT, C1200 F Blend, melt flow rate is 5.5g / 10min), 0.5 parts antioxidant 1010, 0.3 parts chain extender After being fully premixed, ADR-4370 is extruded and granulated by a co-rotating twin-screw extruder (screw diameter 20mm, L / D=40) from Swedish Labtech. The extruder temperatures are 190℃, 200℃, 220℃, 230℃, 235℃, 230℃, 240℃, 240℃, 230℃ and 225℃, and the screw speed is set to 200rpm. During stable operation, the torque is 20-40%. The extruder is equipped with a circular die with a diameter of 3mm. After the strips are extruded from the die and air-cooled, they are cut into cylindrical particles of about 3mm by a pelletizer. The melt flow rate is measured to be 4g / 10min. The particles are collected, dried in a vacuum drying oven at 60℃ for 4h, and then packaged for use.
[0050] [Comparative Example 2]
[0051] Preparation of polyglycolic acid resin composition:
[0052] The polyglycolic acid particles and polybutylene adipate terephthalate particles were dried by hot air at a temperature of 35±2°C for 2 hours. 30 parts of polyglycolic acid (PGA, Corbion Purac) and 70 parts of polybutylene adipate terephthalate (PBAT, C1200F Blend, melt flow rate is 5.5g / 10min), 0.5 parts antioxidant 1010, 0.3 parts chain extender After being fully premixed, ADR-4370 was extruded and granulated by a co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) from Swedish Labtech. The extruder temperatures were 190℃, 200℃, 220℃, 230℃, 235℃, 230℃, 240℃, 240℃, 230℃ and 225℃, and the screw speed was set to 200rpm. During stable operation, the torque was 20-40%. The extruder was equipped with a circular die with a diameter of 3mm. After the strips were extruded from the die and air-cooled, they were cut into cylindrical particles of about 3mm by a pelletizer. The melt flow rate was measured to be 2.5g / 10min. The particles were collected, dried in a vacuum drying oven at 60℃ for 4h, and then packaged for use.
[0053] [Example 1]
[0054] Preparation of polyglycolic acid graft copolymer:
[0055] Polyglycolic acid, vinyl propionate, cumene hydroperoxide and antioxidant 1010 were fully premixed in a mass ratio of 400:16:0.8:0.8, and the grafting reaction was carried out using a co-rotating twin-screw extruder from Swedish Labtech. The rotation speed was 200rpm, and the extrusion temperatures were 190℃, 220℃, 230℃, 240℃, 240℃, 240℃, 240℃, 240℃, 230℃ and 225℃. The extruder was equipped with a circular die with a diameter of 3mm. After the strips were extruded from the die and air-cooled, they were cut into cylindrical yellow particles with a length of about 3mm by a pelletizer, namely polyglycolic acid graft copolymer particles B. After measurement, the melt flow rate was 25.9g / 10min. The particles were collected and packaged for later use. The molecular weight of the graft copolymer was measured by GPC, and the weight average molecular weight (M w ): 125117g / mol, Mn=75095g / mol, PDI=1.67.
[0056] [Example 2]
[0057] Preparation of polyglycolic acid resin composition:
[0058] The polyglycolic acid particles and polybutylene adipate terephthalate particles were dried by hot air at a temperature of 35±2°C for 2 hours. 20 parts of fully dried polyglycolic acid (PGA, Corbion Purac), 5 parts of polyglycolic acid graft copolymer particles B, and 75 parts of polybutylene adipate terephthalate (PBAT, C1200F Blend, melt flow rate is 5.5g / 10min), 0.5 parts antioxidant 1010, 0.3 parts chain extender After being fully premixed, ADR-4370 was extruded and granulated by a co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) from Swedish Labtech. The extruder temperatures were 190℃, 200℃, 220℃, 230℃, 235℃, 230℃, 240℃, 240℃, 230℃ and 225℃, and the screw speed was set to 200rpm. During stable operation, the torque was 20-40%. The extruder was equipped with a circular die with a diameter of 3mm. After the strips were extruded from the die and air-cooled, they were cut into cylindrical particles of about 3mm by a pelletizer. The melt flow rate was measured to be 5.8g / 10min. The particles were collected, dried in a vacuum drying oven at 60℃ for 4h, and then packaged for use.
[0059] [Example 3]
[0060] Preparation of polyglycolic acid resin composition:
[0061] The polyglycolic acid particles and polybutylene adipate terephthalate particles were dried by hot air at a temperature of 35±2°C for 2 hours. 15 parts of polyglycolic acid (PGA, Corbion Purac), 10 parts of PGA modified particles B, and 75 parts of polybutylene adipate terephthalate (PBAT, C1200F Blend, melt flow rate is 5.5g / 10min), 0.5 parts antioxidant 1010, 0.3 parts chain extender After being fully premixed, ADR-4370 was extruded and granulated by a co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) from Swedish Labtech. The extruder temperatures were 190℃, 200℃, 220℃, 230℃, 235℃, 230℃, 240℃, 240℃, 230℃ and 225℃, and the screw speed was set to 200rpm. During stable operation, the torque was 20-40%. The extruder was equipped with a circular die with a diameter of 3mm. After the strips were extruded from the die and air-cooled, they were cut into cylindrical particles of about 3mm by a pelletizer. The melt flow rate was measured to be 6.6g / 10min. The particles were collected, dried in a vacuum drying oven at 60℃ for 4h, and then packaged for use.
[0062] [Example 4]
[0063] Preparation of polyglycolic acid graft copolymer:
[0064] Polyglycolic acid, vinyl propionate, cumene hydroperoxide and antioxidant 1010 were fully premixed in a mass ratio of 800:16:0.8:1.6, and grafting reaction was carried out using a co-rotating twin-screw extruder from Swedish Labtech. The speed was 100rpm, and the extrusion temperatures were 190℃, 220℃, 230℃, 240℃, 240℃, 240℃, 240℃, 240℃, 230℃ and 225℃. The extruder was equipped with a circular die with a diameter of 3mm. After the strip was extruded from the die and air-cooled, it was cut into cylindrical yellow particles with a length of about 3mm by a pelletizer, namely polyglycolic acid graft copolymer particles C. After measurement, its melt flow rate was 23.6g / 10min. The particles were collected and packaged for use. The molecular weight of the graft copolymer was measured by GPC, Mw=115083g / mol, Mn=75095g / mol, PDI=1.67.
[0065] [Example 5]
[0066] Preparation of polyglycolic acid resin composition:
[0067] The polyglycolic acid particles and polybutylene adipate terephthalate particles were dried by hot air at a temperature of 35±2°C for 2 hours. 25 parts of fully dried polyglycolic acid (PGA, Corbion Purac), 5 parts of PGA modified particles C, and 70 parts of polybutylene adipate terephthalate (PBAT, C1200F Blend, melt flow rate is 5.5g / 10min), 0.5 parts antioxidant 1010, 0.3 parts chain extender After being fully premixed, ADR-4370 was extruded and granulated by a co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) from Swedish Labtech. The extruder temperatures were 190℃, 200℃, 220℃, 230℃, 235℃, 230℃, 240℃, 240℃, 230℃ and 225℃, and the screw speed was set to 200rpm. During stable operation, the torque was 20-40%. The extruder was equipped with a circular die with a diameter of 3mm. After the strips were extruded from the die and air-cooled, they were cut into cylindrical particles of about 3mm by a pelletizer. The melt flow rate was measured to be 4.01g / 10min. The particles were collected, dried in a vacuum drying oven at 60℃ for 4h, and then packaged for use.
[0068] [Example 6]
[0069] Preparation of polyglycolic acid resin composition:
[0070] The polyglycolic acid particles and polybutylene adipate terephthalate particles were dried by hot air at a temperature of 35±2°C for 2 hours. 30 parts of fully dried polyglycolic acid (PGA, Corbion Purac), 10 parts of polyglycolic acid graft copolymer particles C, and 60 parts of polybutylene adipate terephthalate (PBAT, C1200FBlend, melt flow rate is 5.5g / 10min), 0.5 parts of antioxidant 1010, 0.3 parts of chain extender After being fully premixed, ADR-4370 was extruded and granulated by a co-rotating twin-screw extruder (screw diameter 16mm, L / D=40) from Swedish Labtech. The extruder temperatures were 190℃, 200℃, 220℃, 230℃, 235℃, 230℃, 240℃, 240℃, 230℃ and 225℃, and the screw speed was set to 200rpm. During stable operation, the torque was 20-40%. The extruder was equipped with a circular die with a diameter of 3mm. After the strips were extruded from the die and air-cooled, they were cut into cylindrical particles of about 3mm by a pelletizer. The melt flow rate was measured to be 9.8g / 10min. The particles were collected, dried in a vacuum drying oven at 60℃ for 4h, and then packaged for use.
[0071] [Example 7]
[0072] Preparation of polyglycolic acid resin composition film samples:
[0073] The polyglycolic acid resin composition particles obtained in Examples 2, 3, 5 and Comparative Examples 1 and 2 were fully dried and then placed in a HAAKE TM The blown films were prepared on a Rheomex OS single screw extruder with a screw diameter of 19 mm, an aspect ratio of 25, and a 3:1 standard metering screw. The extruder was manufactured by HAAKE TM PolyLab TM The extruder is controlled by OS torque rheometer platform. The extruder has four heating sections, numbered 1-4 from the feed port to the outlet, and is equipped with a blown film die with a heating function, a die diameter of 19.5mm, and a die gap of 0.5mm. The screw speed is set to 50rpm, and the temperature of each section is set to: 200℃, 210℃, 220℃ and 220℃. The film is then made into a film through cooling, shaping, drawing and winding. The film thickness is controlled to be around 25μm.
[0074] The polyglycolic acid resin composition particles obtained in Example 6 were fully dried and then HAAKE TM The blown cast film was prepared on a Rheomex OS single screw extruder with a screw diameter of 19 mm, an aspect ratio of 25, and a 3:1 standard metering screw. The extruder was manufactured by HAAKE TM PolyLab TM The OS torque rheometer platform controls the temperature of each section to 200℃, 210℃, 220℃ and 220℃ respectively, and then the film is made by cooling, shaping, stretching and winding. The thickness of the film is controlled to be about 35μm.
[0075] [Test Example 1]
[0076] The polyglycolic acid resin composition particles prepared in Examples 2, 3, 5, 6 and Comparative Examples 1-2 were subjected to thermogravimetric analysis (TGA) according to the above-described steps. The results are as follows: Figure 1 As shown, the thermal decomposition temperature (T d (5%)) The test results are listed in Table 1.
[0077] Table 1. Thermal weight loss temperature of particles in the examples and comparative examples
[0078]
[0079] [Test Example 2]
[0080] The polyglycolic acid resin composition films corresponding to Comparative Examples 1 to 2 and Examples 2, 3, 5, and 6 were subjected to the xenon lamp accelerated aging equipment described above, and the long-term changes of the films before aging and after aging for 100 hours were evaluated by synchrotron radiation small-angle scattering. The results are as follows: Figure 1 As shown. Figure 1 It is obvious that after 100 hours of accelerated aging, the long period of the lamellae corresponding to Example 2 changes the least, with only a change of 0.2 nm, indicating that the graft prepared by the present invention has a stable structure and excellent aging stability.
[0081] [Test Example 3]
[0082] The four polyglycolic acid resin composition films corresponding to Comparative Examples 1 and 2 and Examples 2 and 3 were subjected to the xenon lamp accelerated aging equipment described above to evaluate the retention rate of elongation at break (E(t) / E(0)) at different aging times. The results are as follows: Figure 2 shown.
[0083] Depend on Figure 2 It can be seen that with the extension of aging time, the elongation at break of PGA / PBAT films is significantly reduced. After 24 hours of accelerated aging, the elongation at break retention rate of the film of Example 2 is 95%, while the elongation at break retention rate of the film of Comparative Example 2 is only reduced by 50%. After 48 hours, the elongation at break retention rate of Comparative Example 1 dropped sharply from 94.5% to 53.3%. Under the same aging time, the elongation at break retention rate of the film of Example 2 can reach 71%, and its elongation at break retention rate is 1.3 times and 1.55 times that of the films of Comparative Example 1 and Comparative Example 2, respectively, indicating that the polyglycolic acid resin composition prepared in Example 2 is structurally stable before and after aging, and even after accelerated aging for more than 144 hours, the elongation at break retention rate of the film of Example 1 is still greater than 20%.
[0084] The aging experiment shows that after the vinyl ester / polyglycolic acid graft copolymer is added to the melt blend, the anti-aging performance of the polyglycolic acid blend film is significantly improved. It can be seen that the technical solution of the present invention can achieve the purpose of improving the stability of the polyglycolic acid blend.
Claims
1. An aging-resistant polyglycolic acid resin composition comprising: A mixture of polyglycolic acid, polyglycolic acid graft copolymer, polybutylene terephthalate resin and / or its reaction product, wherein the polyglycolic acid graft copolymer is a copolymer of a vinyl ester compound or its derivative and polyglycolic acid.
2. The polyglycolic acid resin composition according to claim 1, characterized in that Taking the total mass of the polyglycolic acid, the polyglycolic acid graft copolymer and the polybutylene terephthalate resin as 100%, the polyglycolic acid accounts for 8.5-75%, the polyglycolic acid graft copolymer accounts for 0.5-20%, and the polybutylene terephthalate resin accounts for 5-91%; preferably, the polyglycolic acid accounts for 20-55%, the polyglycolic acid graft copolymer accounts for 1-15%, and the polybutylene terephthalate resin accounts for 30-79%.
3. The polyglycolic acid resin composition according to claim 1, characterized in that The weight average molecular weight of the polyglycolic acid is 100,000 to 1,000,000 g / mol, and the molecular weight distribution index is 1.5 to 5; preferably, the weight average molecular weight of the polyglycolic acid is 100,000 to 500,000 g / mol, and the molecular weight distribution index is 2 to 3; and / or, The intrinsic viscosity of the polyglycolic acid is 0.9 to 7 dl / g, preferably 1 to 5 dl / g; and / or, The polyglycolic acid has a melt flow rate of 1 to 80 g / 10 min, preferably 1 to 50 g / 10 min, measured at 230° C. and 2.16 kg; and / or The polybutylene terephthalate resin is selected from the copolyester of aliphatic dibasic acid / terephthalic acid / polyol, preferably at least one of polybutylene adipate terephthalate and polybutylene succinate terephthalate; and / or, The vinyl ester compound or its derivative is selected from fatty acid vinyl ester compounds or their derivatives, preferably at least one selected from vinyl acetate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl octadecanoate, divinyl adipate, and vinyl decanoate; and / or, The weight average molecular weight of the polyglycolic acid graft copolymer is 90,000 to 300,000 g / mol, preferably 110,000 to 200,000 g / mol.
4. The polyglycolic acid resin composition according to claim 1, characterized in that The polyglycolic acid resin composition further comprises a functional additive, and preferably, the functional additive is selected from at least one of antioxidant I and a chain extender.
5. The polyglycolic acid resin composition according to claim 4, characterized in that: The antioxidant I is selected from at least one of hindered phenols, hindered amines, phosphites, phosphates, and thiols; and / or, The chain extender is selected from at least one of multifunctional compounds or grafts containing multiple epoxy groups or isocyanate groups, preferably at least one of diphenylmethane diisocyanate, dioxazoline, glycidyl methacrylate, and styrene-methyl methacrylate-maleic anhydride copolymer; and / or, Based on the total mass of the polyglycolic acid, polyglycolic acid graft copolymer and polybutylene terephthalate resin as 100%, the antioxidant I is 0.1-5%, preferably 0.1-2%; the chain extender is 0.01-10%, preferably 0.01-5%.
6. A method for preparing the aging-resistant polyglycolic acid resin composition according to any one of claims 1 to 5, comprising: The components including the polyglycolic acid, polybutylene terephthalate resin and polyglycolic acid graft copolymer are fully mixed, melt blended and extruded, and cooled to obtain the anti-aging polyglycolic acid resin composition.
7. The preparation method according to claim 6, characterized in that: The polyglycolic acid, polybutylene terephthalate resin and polyglycolic acid graft copolymer are dried before mixing; and / or, The conditions for melt blending and extrusion are: the temperature of melt blending and extrusion is 180-260° C., and the speed of the extruder is 10-500 rpm; preferably, the temperature of melt blending and extrusion is 190-250° C., and the speed of the extruder is 100-250 rpm; and / or, Functional additives are also added during the mixing process.
8. The preparation method according to claim 7, characterized in that: The drying temperature is 10-80°C, preferably 10-40°C.
9. The preparation method according to claim 6, characterized in that: The polyglycolic acid graft copolymer is obtained by mixing a vinyl ester compound or its derivative with polyglycolic acid and subjecting it to a grafting reaction under the action of an initiator; preferably, a screw extruder is used for the melt grafting reaction.
10. The preparation method according to claim 9, characterized in that: The initiator is selected from organic peroxide initiators, preferably at least one selected from tert-butylbenzene peroxide, dibenzoyl peroxide, and dicumyl peroxide; and / or, The mass ratio of the vinyl ester compound or its derivative to the polyglycolic acid is 1:(10-200), preferably 1:(15-80); and / or, Based on the total mass of the vinyl ester compound or its derivative and the polyglycolic acid as 100%, the initiator is 0.01-1%, preferably 0.07-0.2%.
11. The preparation method according to claim 9, characterized in that: The temperature of the grafting reaction is 140 to 260° C., preferably 150 to 240° C.; and / or, Antioxidant II is optionally added during the mixing process. Preferably, the antioxidant II is selected from at least one of hindered phenols, hindered amines, phosphites, phosphates, and thiols; and / or, based on the total mass of the vinyl ester compound or its derivative and polyglycolic acid as 100%, the antioxidant II is 0.1-5%.
12. An aging-resistant polyglycolic acid resin composition according to any one of claims 1 to 5 or an aging-resistant polyglycolic acid resin composition obtained by the preparation method according to any one of claims 6 to 11, characterized in that: After 100 hours of xenon lamp accelerated aging, the elongation at break retention rate of the polyglycolic acid resin composition is greater than 25%, and the long-term period change of the composition is less than or equal to 0.4 nm.
13. Use of the aging-resistant polyglycolic acid resin composition according to claim 12 in packaging materials, injection molded products, agricultural films, and temporary plugging materials for oil production.
Citation Information
Patent Citations
Modified polyglycolic acid biodegradable mulch film and preparation method thereof
CN109575536A